Morphological and Immunophenotypical Changes of Human Bone Marrow Adipocytes in Marrow Metastasis and Myelofibrosis - Dello Spedale Venti, Michele; Palmisano, Biagio; Donsante, Samantha; Farinacci, Giorgia; Adotti, Flavia; Coletta, Ilenia; Serafini, Marta; Corsi, Alessandro; Riminucci, Mara (Frontiers in Endocrinology, 2022)
The bone marrow adipose tissue constitutes more than two-thirds of the bone marrow volume in adult life and is known to have unique metabolic and functional properties. In neoplastic disorders, bone marrow adipocytes (BMAds) contribute to create a favorable microenvironment to survival and proliferation of cancer cells. Many studies explored the molecular crosstalk between BMAds and neoplastic cells, predominantly in ex-vivo experimental systems or in animal models. However, little is known on the features of BMAds in the human neoplastic marrow. The aim of our study was to analyze the in situ changes in morphology and immunophenotype of BMAds in two different types of neoplastic marrow conditions. We selected a series of archival iliac crest and vertebral bone biopsies from patients with bone marrow metastasis (MET), patients with myeloproliferative neoplasia with grade-3 myelofibrosis (MPN-MF) and age-matched controls (CTR). We observed a significant reduction in the number of BMAds in MET and MPN-MF compared to CTR. Accordingly, in the same groups, we also detected a significant reduction in the mean cell diameter and area. Immunolocalization of different adipocyte markers showed that, compared to CTR, in both MET and MPN-MF the percentages of adiponectin- and phosphorylated hormone sensitive lipase-positive BMAds were significantly reduced and increased respectively. No statistically significant difference was found between MET and MPN-MF. Interestingly, in one MET sample, “remodeled” BMAds containing a large lipid vacuole and multiple, smaller and polarized lipid droplets were identified. In conclusion, our data show that in different types of marrow cancers, BMAds undergo significant quantitative and qualitative changes, which need to be further investigated in future studies.